ANALYZING BOND YIELD SPREAD DYNAMICS IN KAZAKHSTAN AND RUSSIA: A STUDY AMID REGIONAL UNCERTAINTIES - Mashirapov, Darkhan (Nazarbayev University Graduate School of Business, 2024)
This thesis examines the determinants of bond yield spreads between corporate and government bonds with maturities of 1, 5, and 10 years in Kazakhstan and Russia. The study utilizes regression analysis to explore how macroeconomic factors and their lags influence these spreads, providing insights into the dynamics of fixed-income markets in both countries. Key explanatory variables include growth rates, macroeconomic ratios such as gross international reserves to GDP, and exchange rate volatilities, among others. A significant component of this research focuses on the geopolitical and economic impact of the Russian invasion of Ukraine, captured through the inclusion of a war dummy variable to assess shifts in bond market behavior post-February 2022. In addition to analyzing bond spreads within each country, the study investigates cross-country dynamics by modeling the differences between Russia's corporate bond index yield and Kazakhstan's corporate bond index yield. To capture the long-term equilibrium relationship between these spreads and macroeconomic determinants, cointegration techniques are used. The findings suggest that macroeconomic indicators, such as GDP growth rates, international reserve ratios, and exchange rate movements, play a critical role in shaping bond yield spreads. Moreover, the results indicate that the Russian invasion of Ukraine significantly altered the determinants and behavior of bond spreads, highlighting the sensitivity of financial markets to geopolitical events. This study contributes to the understanding of bond market dynamics in emerging economies and offers a framework for policymakers and investors to evaluate risk and return in the presence of economic and geopolitical shocks.
Keywords: Bond yield spreads; corporate vs. government bonds; Kazakhstan; Russia; macroeconomic factors; exchange rate volatility; GDP growth; geopolitical impact; Russian-Ukraine war; regression analysis; cointegration; oil prices; risk premiums; investor sentiment; emerging markets; financial volatility.; Type of access: Open